UPAYA MENINGKATKAN AKTIVITAS BERTANYA SISWA DAN PRESTASI BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TUTOR SEBAYA - Antonius Anton; Vigih Hery Kristanto (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
The goals of the research are to improve students’ activity in asking question and to improve the mathematics learning by applying peer tutor cooperative learning. The subject of the research was 24 student of class VII F SMP Negeri 9 Madiun. While the object of the research were the students’ attempts to ask question and the students’ a chievement in learning mathematics. Class-action research was opplied two cyclical times in which a cyclical time consisted of two meeting. The result of class-action research shows that the use of peer tutor cooperative learning increases of cycle 1 to cycle 2. The total average score of the first learning process is 3,28 and the second learning process is 3,33. The observation of students’ inquiry increases from cycle 1 to cycle 2. The percentage of the students’ inquiry for cycle 1 is 47,05 and the second one is 57,39. The accomplished percentage for cycle 1 is 9,09% and for cycle 2 is 30,43%. The result does not show the indicator of accomplishment so that we need another cycle to improve it. Based on the data we can conclude that there is improvement on learning process, students’ inquiry and students’ achievement in mathematics learning from cycle 1 to cycle 2. Peer tutor cooperative learning has not proven the students’ inquiry and the students achievements for class VII F SMP Negeri 9 Madiun. Key Word: Students’ Asking Activity, Mathematics Achievement, Cooperative Learning, Peer Tutor.